Pengembangan Bahan Ajar Berbasis Cabri 3D Materi Dimensi Tiga Kelas X SMA - Drajat Friansah; Zulkardi Zulkardi; Somakim Somakim (Universitas Hamzanwadi, 2015)
This study aims to (1) produce teaching materials based Cabri 3D material Three Dimensrions which is valid, practical, has a potential effect on the achievement of learning and explain the process of development, (2) describe the characteristics of teaching materials based Cabri 3D material Three Dimensions. In developing teaching materials, researchers through the preliminary stage and prototyping with groove formative evaluation. In the prototyping stage researchers involved class X SMA Xavierus Lubuklinggau. Data collection techniques used are documentation, walk-throughs, and the results of the test. This research-based teaching materials Cabri produce 3D material Three Dimensions valid and practical, and has a potential effect on the achievement of learning and self-sufficiency indicators of student learning. Validity of instructional materials in terms of compliance with the curriculum and the results of expert validation and test prototypes at the stage of a small group. The potential effect of this teaching material visible from the ability of students determines the position, distance and angle of the elements of geometry. The results of the evaluation study shows 3.13% category excellent value, 56.25 Good, 34.38 Enough, and 6.25 Less. From the observation unstructured during the learning process of students have the initiative to learn and utilize learning resources.